Model Development of U-turn Capacity Using Simulation and Empirical Approaches - Mohammed, Hussein Kariem (Nahrain University College of Engineering Journal, 2008)
In this study, both empirical and simulation approaches were used to estimate capacity of U-turn movement at median openings of divided arterials. The empirical approach using regression analysis was adopted to estimate the best form of the predictive equation for the U-turn capacity and investigate theeffect of different relevant factors that might affect the estimated capacity. Simulation approach was used also to calculate capacity on the basis of the U-SIMmodel; this model represents the traffic performance at U-turn median openings and calculates the number of turning vehicles with respect to a differentconflicting traffic stream. The results of both approaches were compared and presented in this study. A linear model was also recommended as arelationship between the average total delay of the Uturning vehicles and the conflicting traffic flow